First two bilateral hand transplantations in India (Part 2): Technical details - Sharma, Mohit; Iyer, Subramania; P., Kishore; Mathew, Jimmy; Reddy, Raghuveer; Ramu, Janarthanan; Vijayaraghavan, Sundeep; Wakure, Abhijeet; M., Chetan Mali S; Varma, Visakh; Chaudhari, Ashish; Dhake, Swapnil; Omkumar, Akshay; Paul, Jerry; Rajan, Sunil; Nair, Ayyappan; Shaji, Druvan (Indian Journal of Plastic Surgery, 2017)
Introduction: This article deals with two patients who underwent bilateral hand transplantation following amputation of both upper limbs at the distal third of the foream. Materials and Methods: The first patient had a history of loss of hands in a train accident, with possiblity of a run over element during the injury. The second patient lost his both hands in a mine blast. The preoperative work up included detailed clinical and psychological evaluation. The donor retrieval was similar in both the cases and the donors were housed in our own instittution. The donor preparation, recipient preparation and the transplant procedure was similar except for the need of primary tendon transfers in the left hand of the first patient. Results: The first patient needed a free flap transfer to cover compromised skin flap on the left hand on the second day. The second hand transplant was uneventful. Both the recipients are now back to their normal daily routines. Conclusions: Hand transplantation is a potentially life altering procedure, but to optimise the results, it is imperative that there is a meticulous planning and diligent execution with utmost importance to the detail coupled with a synchronised team effort.
Keywords: Composite tissue allotransplantation; hand transplantation; technical details; vascular composite tissue allotransplantation